DEPICTION OF LONELY WOMEN IN KATHERINE MANSFIELD’S SHORT STORIES: PSYCHOLOGICAL FEATURES OF LONELY CHARACTERS - RAJABOVNA, KILICHEVA MEKHRINISO (International Journal of Psychosocial Rehabilitation, 2020)
In the twentieth century literature the motif of loneliness became a predominant theme in many modern writers’ works, especially in Katherine Mansfield’s short stories. This paper draws some views about psychological state of lonely characters. Lonely woman characters of “Miss Brill”, “Life of Ma Parker”, “Canary”, “The Woman at the Store” are analyzed in this paper and some conclusions are given about their psychological features.